An Analysis of Aesthetic Communication on Wayang Tavip’s Performance to Influence Public Understanding - Riana, Irpan; Syah Putra, Yuda (JOMANTARA, 2024)
This research discusses the Wayang Tavip performance with a focus on the analysis of aesthetic communication in a public context. The research method used is descriptive to gain an in-depth understanding of the aesthetic aspects contained in the Wayang Tavip performance. Wayang Tavip is an art form that combines traditional elements with a modern public context. This study identifies aesthetic elements such as visual design, color usage, stage arrangement, and artistic expression used in the Wayang Tavip performance. Additionally, this research explores how aesthetic communication in the Wayang Tavip performance can influence the audience in a public context. The results of the study show that the Wayang Tavip performance possesses aesthetic richness that creates a deep visual and emotional experience for the audience. The aesthetics presented in this performance have the potential to enrich and expand the public's understanding of traditional art, while also attracting the attention of the younger generation.